2001
DOI: 10.1073/pnas.131192798
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the regulatory subunit H of the V-type ATPase of Saccharomyces cerevisiae

Abstract: In contrast to the F-type ATPases, which use a proton gradient to generate ATP, the V-type enzymes use ATP to actively transport protons into organelles and extracellular compartments. We describe here the structure of the H-subunit (also called Vma13p) of the yeast enzyme. This is the first structure of any component of a V-type ATPase. The H-subunit is not required for assembly but plays an essential regulatory role. Despite the lack of any apparent sequence homology the structure contains five motifs simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
128
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(134 citation statements)
references
References 44 publications
6
128
0
Order By: Relevance
“…The monomeric GGAs are a multidomain protein family implicated in protein trafficking between the Golgi and endosomes. Previous structural analysis shows that the small 18-kDa VHS domain of the Hrs protein consists of three HEAT or ARM repeats (Mao et al, 2000), a protein fold that has been recently found also in the structure of the regulatory subunit H of the V-ATPase (Sagermann et al, 2001). On the basis of the sequence similarity found, we conclude that also ␤-adaptins and ␤-COP are HEAT or ARM repeat-containing proteins.…”
Section: Molecular Biology Of the Cell 2052supporting
confidence: 66%
See 4 more Smart Citations
“…The monomeric GGAs are a multidomain protein family implicated in protein trafficking between the Golgi and endosomes. Previous structural analysis shows that the small 18-kDa VHS domain of the Hrs protein consists of three HEAT or ARM repeats (Mao et al, 2000), a protein fold that has been recently found also in the structure of the regulatory subunit H of the V-ATPase (Sagermann et al, 2001). On the basis of the sequence similarity found, we conclude that also ␤-adaptins and ␤-COP are HEAT or ARM repeat-containing proteins.…”
Section: Molecular Biology Of the Cell 2052supporting
confidence: 66%
“…The crystal structure of the yeast homologue of subunit H, VMA13p, was published recently (Sagermann et al, 2001). Although the yeast homologue VMA13p contains only 21.7% sequence identity to human V1H, a structure-based alignment enabled us to transform the secondary structure elements of VMA13p to V1H ( Figure 1B).…”
Section: Molecular Characterization Of V1hmentioning
confidence: 99%
See 3 more Smart Citations